Impact of digital transformation on renewable energy companies’ performance: Evidence from China - Ren, Yangjun; Li, Botang; Liang, Dong (Frontiers in Environmental Science, 2023)
The rapid development of the renewable energy industry provides essential opportunities for China to achieve the goal of carbon peaking and carbon neutrality. A rising number of renewable energy companies are positively embracing digital transformation in the digital age. However, the relationship between digital transformation and the performance of renewable energy companies remains unclear. To fill this gap, we investigate the influence of digital transformation on firm performance using a panel data of Chinese A-share listed renewable energy companies. Leveraging the latest advances in textual analysis, we quantify the extent of a renewable energy enterprise’s digital transformation. The results indicate that digital transformation enhances a renewable energy enterprise’s performance. Further, the promotion effect of digital transformation is greater among state-owned enterprises and large firms and is only helpful for firms in the eastern area. Moreover, we document that when a renewable energy enterprise adopts digital transformation, it has higher operating efficiency, lower cost, and better innovation success resulting in better performance. This research elucidates the role of digital transformation in improving the growth of renewable energy enterprises and bears significant policy implications.